2014
DOI: 10.1136/bcr-2013-202408
|View full text |Cite
|
Sign up to set email alerts
|

Renal abscesses in childhood: report of two uncommon cases

Abstract: Renal abscesses are rare conditions in children, but they must be remembered in differential diagnosis of fever and abdominal pain. The authors report two paediatric cases with unusual presentation. Case 1: a 15-year-old girl was admitted following a period of fever, vomiting and left hypochondrium pain which became more localised to the left lower ribs. Blood tests suggested bacterial infection, but urinalysis and culture were negative. Renal CT scan presented features of bilateral pyelonephritis and left ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 9 publications
0
9
0
8
Order By: Relevance
“…La sintomatología del absceso renal es vaga, con o sin fiebre, dolor abdominal o lumbar, náuseas/vómito, apariencia enferma y a nivel de laboratorio el cuadro hemático muestra leucocitosis, hay elevación de los reactantes de fase aguda, que se puede confundir con facilidad con una pielonefritis, lo cual puede retardar el diagnóstico (5-7), datos que coinciden con los casos que reportamos. También puede presentarse como un síndrome febril de causa desconocida, asociado a malestar general, y es necesario un alto índice de sospecha (7). La media de duración de los síntomas previa al diagnóstico es de diez días (5).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…La sintomatología del absceso renal es vaga, con o sin fiebre, dolor abdominal o lumbar, náuseas/vómito, apariencia enferma y a nivel de laboratorio el cuadro hemático muestra leucocitosis, hay elevación de los reactantes de fase aguda, que se puede confundir con facilidad con una pielonefritis, lo cual puede retardar el diagnóstico (5-7), datos que coinciden con los casos que reportamos. También puede presentarse como un síndrome febril de causa desconocida, asociado a malestar general, y es necesario un alto índice de sospecha (7). La media de duración de los síntomas previa al diagnóstico es de diez días (5).…”
Section: Discussionunclassified
“…Nuestros aislamientos fueron de E. coli. En la literatura se ha reportado que los microorganismos Gram negativos, especialmente la E. coli, son los patógenos más comúnmente encontrados si hay una infección urinaria previa (7), aislándose algunas veces cepas productoras de BLEE (13). El S. aureus predomina cuando la diseminación es hematógena (14), aunque también puede ser ocasionada por streptococcus (infecciones de la piel y tejidos blandos, dentales, del tracto respiratorio, intraabdominales, cardiacas, genitales, relacionadas a catéteres intravasculares o uso de drogas ilícitas intravenosas) (12).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Gram negative organisms (E. coli) typically have direct spread (ascending infection) and Gram-positive organisms (S. aureus) typically have hematogenous spread. Less than half of cases ever develop a positive blood or urine culture (15). A high index of suspicion is required to make early diagnosis and prevent renal scarring.…”
Section: Discussionmentioning
confidence: 99%
“…This report showed Escherichia coli was the most common pathogen isolated (37%), only one case was pyelonephritis from Proteus mirabilis (3). Cancelinha. C et al (2014) reported two uncommon case of renal abscess from Proteus mirabilis in childhood.…”
Section: Pathology and Histopathology Reportmentioning
confidence: 99%